Perancangan Tekstil Permukaan Bermotif Rajamala Melalui Teknik Digital Printing Pada Pembuatan Kemeja Casual - Kristiyanto, Priska Nanette; Endah Santoso, Ratna (Hastagina : Jurnal Kriya Seni, 2025)
Starting from a love and hobby of photography by traveling to enjoy the beauty of the city of Solo, which has a diverse history and art, became one of the driving forces to realize the development of motif designs inspired by Rajamala. This design explores the potential of digital printed surface textiles combined with Rajamala to educate the public regarding local culture through casual shirt products. The resulting digital printing design is a combination of Rajamala and photos of iconic places in the city of Solo which are processed with a contemporary and modern style to attract the attention of the wider community to preserve local culture in a unique and interesting way. The design method used follows Bram Palgunadi's approach, which involves four main stages, namely the research process, analysis, concept preparation, design planning and product creation. Each stage is carried out in three steps, namely exploration, extraction and termination. The results of this design are six designs inspired by Rajamala motifs using digital surface textile printing techniques. This digital printing motif was applied as casual shirts for men and women, both teenagers and adults with two designs realized as shirt products, and one design realized as a cloth product. The design of Rajamala's visual processing using digital sublimation printing offers a different sensation from the existing Rajamala digital printing motifs. The resulting visuality becomes the value of novelty, uniqueness and product differentiation. The results of this design can also be a unique new choice for people who want original local souvenirs that convey art and culture in a casual shirt.